2015
DOI: 10.1002/jpoc.21173
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Challenges Minority Men and Women Experienced With Senior Executive Service Advancement

Abstract: Despite the progress made in diversity hiring and promotion initiatives, minority men and women in the federal government remain underrepresented in the senior executive service workforce. An exploratory case study of 12 minority men and 12 minority women in a federal agency described and explored the perceived personal barriers and challenges experienced with SES advancement. The subfocus explored the perceived influence of support received from agency leaders on SES career advancement. This study was grounde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Studies have revealed that there is an impact of leadership in psychological capital [2]. Women leadership is one type of the leadership administration types that affects psychological capital because it represents a set of characteristics that enable women to make their own decisions and increase their self-confidence to assume leadership and managerial positions and to develop their ability to achieve superior performance [3].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have revealed that there is an impact of leadership in psychological capital [2]. Women leadership is one type of the leadership administration types that affects psychological capital because it represents a set of characteristics that enable women to make their own decisions and increase their self-confidence to assume leadership and managerial positions and to develop their ability to achieve superior performance [3].…”
Section: Introductionmentioning
confidence: 99%